KEMAMPUAN MANAJERIAL DAN AGRESIVITAS PAJAK : STUDI PADAPERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2019-2024) - Anti Anti; Andi Arman; Mira Mira (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to examine the effect of managerial ability on tax aggressiveness in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. In addition to the independent variable of managerial ability proxied by Asset Turnover (ATO), this study also employs control variables including profitability (Return on Assets), firm size, leverage (DER), capital expenditure, and SG&A expenses. The research method used is quantitative with a purposive sampling technique, resulting in a total of 198 observations from 33 manufacturing companies over six years of observation. Data analysis was conducted using panel data regression with the Pooled OLS model using EViews 13 software. The results showed that the independent variable of managerial ability has no significant effect on tax aggressiveness. Similarly, the control variables of profitability, firm size, leverage, capital expenditure, and SG&A expenses all showed no significant effect on the level of tax aggressiveness of manufacturing companies in Indonesia during the observation period. The Adjusted R-squared value of 0.89% indicates that the research model has a very low ability to explain the variation in tax aggressiveness, while the remaining 99.11% is influenced by other factors outside the research model.